Primary Care-Based Hepatitis C Treatment Outcomes With First-Generation Direct-Acting Agents. Issue 5 (September 2015) - Woodrell, Christopher; Weiss, Jeffrey; Branch, Andrea; Gardenier, Donald; Krauskopf, Katherine; Kil, Natalie; Paredes, Harold; Bichoupan, Kian; Sigel, Keith
Abstract : Objectives: Vulnerable, urban populations with a history of substance use disorders have a high prevalence of hepatitis C virus (HCV). Primary care-based treatment has been proposed to improve access to care. In this study, we present outcomes from our urban, primary care-based HCV treatment program in patients treated with telaprevir or boceprevir in combination with pegylated-interferon and ribavirin ("triple therapy"). Methods: We collected data from 126 consecutive patients with genotype 1 HCV monoinfection seen in our treatment program (2011–2013). Among the 40 who initiated treatment, we analyzed factors associated with achieving a sustained viral response (SVR). Results: During the study period, 40 patients initiated triple therapy (32%), 80% with recent or past substance use disorders. Patients initiating treatment were younger than untreated patients ( P  = 0.002), but otherwise did not differ demographically, or in the severity of their liver fibrosis ( P  > 0.05). An SVR was achieved in 18 patients (45%) and was less likely in patients with recent or past substance use disorders or psychiatric illness (both P  < 0.01). Conclusions: Nearly one third of patients initiated triple therapy with SVR rates comparable to other HCV treatment settings, despite a significant burden of mental illness and substance dependence. Our experience demonstrates that a primary care-based practice can successfully deliver HCV care to a vulnerable population. Additional interventions may be needed to improve outcomes in patients with recent or past substance use disorders or psychiatric illness.